Construction of xylose assimilating yeast hybrids Through genome shuffling (Funded Work) - J. KARUNA DEVI,; N. SAI KISHORE, (International Journal of Pharma and Bio Sciences, 2017)
Production of bioethanol from lignocellulosic biomass is gaining much research interest because of its abundant supply. Saccharomyces cerevisiae is The commonly used industrial yeast for ethanol production but it lacks the property to ferment pentose sugars mainly xylose present in lignocellulosic materials. In this study, the hybrid yeast strains are developed by genome shuffling process between the xylose sugar fermenting yeast Pichia stipitis and hexose sugar fermenting yeast Saccharomyces cerevisiae. Lyticase enzyme is used to establish viable protoplasts from both the parental yeast strains. Factors affecting physic chemical properties viz., protoplast isolation, enzyme concentration and incubation time were investigated. The optimal parameter for the protoplast release of S. cerevisiae and P. stipitis include 700 µg/µl Lyticase for 60 min and 700 µg/µL Lyticase for 120 min respectively. The maximum protoplast formation ratios were 98.75% and 82.24% for S. cerevisiae and P. stipitis respectively. The frequency of the protoplast fused hybrids was carried out by using Polyethylene Glycol (PEG) as fusogen. Fused hybrids were produced by use of 35% (w/v) PEG 4000, optimized conditions of protoplasts fusion of S.cerevisiae and P. stipitis genome shuffling was achieved at a rate of 80.90% with fusion of 20 min. Further, these hybrids produced through genome shuffling will be further evaluated for production of bioethanol using lignocellulosic materials.